New fossil records of Xyelidae (Hymenoptera) from the Middle Jurassic of Inner Mongolia, China - Zheng, Yan; Hu, Haiyan; Chen, Dong; Chen, Jun; Zhang, Haichun; Rasnitsyn, Alexandr P. (European Journal of Taxonomy, 2021)
A new genus and two new species of Xyelidae Newman, 1834 (Hymenoptera Linnaeus, 1758), Platyxyela tenuis sp. nov. and Scleroxyela daohugouensis gen. et sp. nov. are described and illustrated from the Middle Jurassic Daohugou Beds of Ningcheng, Inner Mongolia, China. Platyxyela tenuis sp. nov. (Xyelinae Newman, 1834, Liadoxyelini Rasnitsyn, 1966) can be distinguished from its congeners by short forewing length and ovipositor sheath strongly narrowed toward acute apex. Scleroxyela daohugouensis gen. et sp. nov. is placed within Macroxyelinae Ashmead, 1898, Xyeleciini Benson, 1945 based on pterositigma completely sclerotised and costal space sclerotised before ptrostigma, 1-Rs half as long as 1-M, and 1m-cu short. It is the first recorded species of Xyeleciini in Daohugou Beds. Furthermore, an updated key of identification of subfamilies and tribes of Xyelidae is provided. Our findings of new morphological data provide insights into the early evolution of Hymenoptera, as well as effectively enrich our understanding of the diversity of Xyelidae in the Mesozoic. A correction has been published: Zheng Y., Hu H., Chen D., Chen J., Zhang H. & Rasnitsyn A.P. 2023. New fossil records of Xyelidae (Hymenoptera) from the Middle Jurassic of Inner Mongolia, China – Corrigendum. European Journal of Taxonomy 860: 181–182. https://doi.org/10.5852/ejt.2023.860.2059